New improved radiometabolite analysis method for [18F]FTHA from human plasma : a test-retest study with postprandial and fasting state - Aarnio, Richard; Kirjavainen, Anna; Rajander, Johan; Forsback, Sarita; Kalliokoski, Kari; Nuutila, Pirjo; Milicevic, Zvonko; Coskun, Tamer; Haupt, Axel; Laitinen, Iina; Haaparanta-Solin, Merja (Springer Nature, 2025)
Background
Fatty acid uptake can be measured using PET and 14-(R,S)‐[18F]fluoro‐6‐thia‐heptadecanoic acid ([18F]FTHA). However, the relatively rapid rate of [18F]FTHA metabolism significantly affects kinetic modeling of tissue uptake. Thus, there is a need for accurate chromatographic methods to analyze the unmetabolized [18F]FTHA (parent fraction). Here we present a new radiometabolite analysis (RMA) method, with comparison to a previous method for parent fraction analysis, and its use in a test-retest clinical study under fasting and postprandial conditions. We developed a new thin-layer chromatography (TLC) RMA method for analysis of [18F]FTHA parent fraction and its radiometabolites from plasma, by testing stationary phases and eluent combinations. Next, we analyzed [18F]FTHA, its radiometabolites, and plasma radioactivity from subjects participating in a clinical study. A total of 17 obese or overweight participants were dosed with [18F]FTHA twice under fasting, and twice under postprandial conditions and plasma samples were obtained between 14 min (mean of first sample) and 72 min (mean of last sample) post-injection. Aliquots of 70 plasma samples were analyzed using both methods, enabling head-to-head comparisons. We performed test-retest and group comparisons of the parent fraction and plasma radioactivity.
Results
The new TLC method separated seven [18F]FTHA radiometabolite peaks, while the previous method separated three. The new method revealed at least one radiometabolite that was not previously separable from [18F]FTHA. From the plasma samples, the mean parent fraction value was on average 7.2 percentage points lower with the new method, compared to the previous method. Repeated [18F]FTHA investigations on the same subject revealed reproducible plasma SUV and parent fractions, with different kinetics between the fasted and postprandial conditions.
Conclusions
The newly developed improved radio-TLC method for [18F]FTHA RMA enables accurate parent fraction correction, which is required to obtain quantitative data for modelling [18F]FTHA PET data. Our test-retest study of fasted and postprandial conditions showed robust reproducibility, and revealed clear differences in the [18F]FTHA metabolic rate under different study settings.
Trial registration
EudraCT No: 2020-005211-48, 04Feb2021; and Clinical Trials registry NCT05132335, 29Oct2021, URL: https://classic.clinicaltrials.gov/ct2/show/NCT05132335.